Bacterial adhesion on conventional and self-ligating metallic brackets after surface treatment with plasma-polymerized hexamethyldisiloxane - Tupinambá, Rogerio Amaral; Claro, Cristiane Aparecida De Assis; Pereira, Cristiane Aparecida; Nobrega, Celestino José Prudente; Claro, Ana Paula Rosifini Alves (Dental Press International, 2017)
ABSTRACTIntroduction:Plasma-polymerized film deposition was created to modify metallic orthodontic brackets surface properties in order to inhibit bacterial adhesion.Methods:Hexamethyldisiloxane (HMDSO) polymer films were deposited on conventional (n = 10) and self-ligating (n = 10) stainless steel orthodontic brackets using the Plasma-Enhanced Chemical Vapor Deposition (PECVD) radio frequency technique. The samples were divided into two groups according to the kind of bracket and two subgroups after surface treatment. Scanning Electron Microscopy (SEM) analysis was performed to assess the presence of bacterial adhesion over samples surfaces (slot and wings region) and film layer integrity. Surface roughness was assessed by Confocal Interferometry (CI) and surface wettability, by goniometry. For bacterial adhesion analysis, samples were exposed for 72 hours to a Streptococcus mutans solution for biofilm formation. The values obtained for surface roughness were analyzed using the Mann-Whitney test while biofilm adhesion were assessed by Kruskal-Wallis and SNK test.Results:Significant statistical differences (p< 0.05) for surface roughness and bacterial adhesion reduction were observed on conventional brackets after surface treatment and between conventional and self-ligating brackets; no significant statistical differences were observed between self-ligating groups (p> 0.05).Conclusion: Plasma-polymerized film deposition was only effective on reducing surface roughness and bacterial adhesion in conventional brackets. It was also noted that conventional brackets showed lower biofilm adhesion than self-ligating brackets despite the absence of film.

RESUMOIntrodução:a deposição de filme de polímero a plasma foi criada para modificar as propriedades de superfície dos braquetes ortodônticos metálicos, com o intuito de inibir a adesão bacteriana.Métodos: filmes finos de polímero de hexametildisiloxano (HMDSO) foram depositados em braquetes ortodônticos de aço inoxidável convencionais (n = 10) e autoligáveis (n = 10), utilizando a técnica de radiofrequência PECVD (Plasma-Enhanced Chemical Vapor Deposition). As amostras foram divididas em dois grupos, de acordo com o tipo de braquete, e dois subgrupos após o tratamento de superfície. A microscopia eletrônica de varredura (MEV) foi realizada para avaliar a presença de adesão bacteriana sobre as superfícies das amostras (região de ranhura horizontal e aletas) e a integridade da camada de filme. A Interferometria Confocal (CI) avaliou a rugosidade, e a molhabilidade superficial foi avaliada por goniometria. Para análise de adesão bacteriana, as amostras foram expostas durante 72 horas a uma solução de Streptococcus mutans, para formação de biofilme. Os valores obtidos para a rugosidade da superfície foram analisados pelo teste de Mann-Whitney, enquanto a adesão do biofilme foi avaliada pelos testes de Kruskal-Wallis e SNK.Resultados: observaram-se diferenças estatisticamente significativas (p <0,05) para a rugosidade superficial e redução da adesão bacteriana em braquetes convencionais após o tratamento da superfície, e entre braquetes convencionais e autoligáveis. Não foram observadas diferenças estatísticas significativas entre os grupos autoligáveis (p> 0,05).Conclusão: a deposição de polímero a plasma só foi efetiva na redução da rugosidade superficial e adesão bacteriana em braquetes convencionais. Observou-se, também, que os braquetes convencionais apresentaram menor adesão ao biofilme do que os braquetes autoligáveis, apesar da ausência de filme.
Keywords: Orthodontic brackets; Bacterial adhesion; Hexamethyldisiloxane.; Braquetes ortodônticos; Adesão bacteriana; Hexametildissiloxano.